Chip-based label-free incoherent super-resolution optical microscopy - Nikhil Jayakumar; Luis E. Villegas-Hernández; Weisong Zhao; Hong Mao; Firehun T. Dullo; Jean-Claude Tinguely; Krizia Sagini; Alicia Llorente; Balpreet Singh Ahluwalia (Light: Science & Applications)
Abstract The photo-kinetics of fluorescent molecules have enabled the circumvention of the far-field optical diffraction limit. Despite its enormous potential, the necessity to label the sample may adversely influence the delicate biology under investigation. Thus, continued development efforts are needed to surpass the far-field label-free diffraction barrier. The statistical similarity or finite coherence of the scattered light off the sample in label-free mode hinders the application of existing super-resolution methods based on incoherent fluorescence imaging. In this article, we present physics and propose a methodology to circumvent this challenge by exploiting the photoluminescence (PL) of silicon nitride waveguides for near-field illumination of unlabeled samples. The technique is abbreviated EPSLON, Evanescently decaying Photoluminescence Scattering enables Label-free Optical Nanoscopy. We demonstrate that such an illumination has properties that mimic the photo-kinetics of nano-sized fluorescent molecules, i.e., such an illumination permits incoherence between the scattered fields from various locations on the sample plane. Thus, the illumination scheme enables the development of a far-field label-free incoherent imaging system that is linear in intensity and stable over time, thereby permitting the application of techniques like structured illumination microscopy (SIM) and intensity-fluctuation-based optical nanoscopy (IFON) in label-free mode to circumvent the diffraction limit. In this proof-of-concept work, we observed a two-point resolution of $$\sim$$ ~ 180 nm on super-resolved nanobeads and resolution improvements between 1.9× to 2.8× over the diffraction limit, as quantified using Fourier Ring Correlation (FRC), on various biological samples. We believe EPSLON is a step forward within the field of incoherent far-field label-free super-resolution microscopy that holds a key to investigating biological systems in their natural state without the need for exogenous labels.